BS EN ISO 21219-19. Intelligent transport systems. Traffic and travel information (TTI) via transport protocol experts group, generation 2 (TPEG2). Part 19. Weather information (TPEG2-WEA) (28th July 2020) - British Standards Institution,
No abstract available